Molecular and structural analysis of central transport channel in complex with Nup93 of nuclear pore complex. (16th November 2020) - Sonawane, Parshuram J.; S. Dewangan, Pravin; Madheshiya, Pankaj Kumar; Chopra, Kriti; Kumar, Mohit; Niranjan, Sangeeta; Ansari, Mohammed Yousuf; Singh, Jyotsana; Bawaria, Shrankhla; Banerjee, Manidipa; Chauhan, Radha
ABSTRACT: The central transport channel (CTC) of nuclear pore complexes (NPCs) is made up of three nucleoporins Nup62, Nup58 and Nup54. In which manner and capacity, these nucleoporins form the CTC, is not yet clear. We explored the CTC Nups from various species and observed that distinct biochemical characteristics of CTC Nups are evolutionarily conserved. Moreover, comparative biochemical analysis of CTC complexes showed various stoichiometric combinations of Nup62, Nup54 and Nup58 coexisting together. We observed the conserved amino‐terminal domain of mammalian Nup93 is crucial for the anchorage of CTC and its localization to NPCs. We could reconstitute and purify mammalian CTC·Nup93 quaternary complex by co‐expressing full length or N‐terminal domain of Nup93 along with CTC complex. Further, we characterized CTC·Nup93 complex using small angle X‐ray scattering and electron microscopy that revealed a "V" shape of CTC·Nup93 complex. Overall, this study demonstrated for the first time evolutionarily conserved plasticity and stoichiometric diversity in CTC Nups.